Separation of variables in the Klein-gordon equations. III; Soviet Physics Journal; Vol. 17, iss. 6 - Bagrov V. G. Vladislav Gavriilovich; Meshkov A. G.; Shapovalov V. N.; Shapovalov A. V. Aleksandr Vasilyevich (1974, 1974)
Title screen